A Bibliometric Analysis of Covid-19 Research using VOSviewer - Hamidah, Ida; Sriyono, Sriyono; Hudha, Muhammad Nur (Universitas Pendidikan Indonesia, 2020)
The new Coronavirus (namely Covid-19) discovered in 2019 in Wuhan has sickened more than three million people in worldwide. Because Covid-19 is spreading so fast and killing so many people, it has encouraged researchers to conduct research and publish it in various mass media, including journals. This study aims to analyze the scope of Covid-19 research using a bibliometric review. To obtain information about Covid-19 studies, the Scopus database was used. Topic areas with titles, keywords, and abstract criteria in Covid-19 studies were used as a reference for extracting search results. Search result extraction was done using VOSviewer. After that, the results of bibliometric mapping were analyzed further. A total of 3,513 articles were found in the Scopus database accessed on April 25, 2020. There was a significant increase in the number of publications on Covid-19 from 2019 to 2020. Among all countries, China contributed the most publications. Meanwhile, the keywords coronavirus, pandemic, and impact turned out to be the area's most widely discussed. Through VOSViewer we analyzed how many articles have been published about Covid-19 and its relationships to a topic area. This review certainly can provide a reference point for further research related to the Covid-19 outbreak.